Acute and subacute dermal toxicity of ethanolic extract of Melastoma malabathricum leaves in Sprague-Dawley rats - Reduan, Farhan Hanif (Toxicol Res, 2020)
Melastoma malabathricum is a well-known herb in Malaysia where it being used in various ways for treatment of different diseases and ailments including skin problems. The study aims to investigate acute and subacute dermal toxicity of ethanolic extract of M. malabathricum leaves following to a single or repeated doses exposure. A total of 30 female Sprague-Dawley rats were grouped into 5 groups (n = 6 per group) for both acute and subacute toxicity study. The duration for each study was determined at 14 days for acute toxicity and 28 days for subacute toxicity. The rats were topically applied with the plant extract at three different doses; 2.5%, 5.0% and 10.0% on the shaved area of dorsal skin. For acute toxicity study, rats in all three groups received single application of the extract on the first day of the experimental period, while rats in subacute toxicity study were topically applied with the extract once daily for 28 days. Throughout the respective 14-day and 28-day study periods, all rats were monitored for any changes in their physical appearance and behavioural patterns that might develop due to toxic effects of the plant. There were no mortality or abnormal physical appearance, and physiological and behavioural changes observed in all rats in both studies. Body weights, kidney and liver weights, and both haematology and serum biochemistry results showed no significant (p > 0.05) differences between all groups in both studies. All of the findings were supported by normal macroscopic and microscopic architectures of liver, kidneys and skin of all rats applied topically with the extract. This study suggests that topical application of M. malabathricum leaf ethanolic extract at 2.5%, 5% and 10% does not induce acute and subacute adverse effects on the skin or systemic toxic reactions in rats.